Influence of phase correction on the acoustic impedance of circular planar sources - KOS, Paweł; LENIOWSKA, Lucyna (Archives of Acoustics, 2007)
In this work, the influence of velocity distribution phase correction on the acoustic impedance of a circular source located in an infinite baffle is analyzed. It has been observed that by turning back a velocity distribution phase by modifying the radiating surface shape in a special way, obtaining a more coherent acoustic radiation is possible. This problem has been analyzed during earlier investigations, with attention focused on the directivity of some acoustic sources [1]. The aim of this paper is to calculate the acoustic impedance which allows the examination of such a ``phase correction’’ effect on the acoustic radiation of the considered sound sources. The result was achieved by numerical calculation with the use of Hankel representation of the acoustic impedance.